O-233 Micronized progesterone plus dydrogesterone versus micronized progesterone alone for luteal phase support in frozen-thawed cycles: a prospective cohort study. (6th August 2021) - Ho, T; Pham, T; Le, K; Ly, T; Le, H; Nguyen, D; Ho, V; Dang, V; Phung, T; Norman, R; Mol, B; Vuong, L
Abstract: Study question: Does the addition of oral dydrogesterone to vaginal progesterone as luteal phase support improve pregnancy outcomes during frozen embryo transfer (FET) cycles compared with vaginal progesterone alone? Summary answer: Luteal phase support with oral dydrogesterone added to vaginal progesterone improves live birth rates and reduces miscarriage rates compared with vaginal progesterone alone. What is known already: Progesterone is an important hormone that triggers secretory transformation of the endometrium to allow implantation of the embryo. During in vitro fertilization (IVF), exogenous progesterone is administered for luteal phase support. However, there is wide inter-individual variation in absorption of progesterone via the vaginal wall. Oral dydrogesterone is effective and well tolerated when used to provide luteal phase support after fresh embryo transfer. However, there are currently no data on the effectiveness of luteal phase support with the combination of dydrogesterone with vaginal micronized progesterone compared with vaginal micronized progesterone after FET. Study design, size, duration: Prospective cohort study conducted at an academic infertility center in Vietnam from 26 June 2019 to 30 March 2020. Participants/materials, setting, methods: We studied 1364 women undergoing IVF with FET. The luteal support regimen was either vaginal micronized progesterone 400 mg twice daily plus oral dydrogesterone 10 mg twice daily (second part of the study) or vaginal micronized progesterone 400 mg twice daily (first 4 months of the study). The primary endpoint was live birth after the first FET of the started cycle, with miscarriage <12 weeks as one of the secondary endpoints. Main results and the role of chance: The vaginal progesterone + dydrogesterone group and vaginal progesterone groups included 732 and 632 participants, respectively. Live birth rates were 46.3% versus 41.3%, respectively (rate ratio [RR] 1.12, 95% confidence interval [CI] 0.99–1.27, p = 0.06; multivariate analysis RR 1.30 (95% CI 1.01–1.68), p = 0.042), with a statistically significant lower rate of miscarriage at < 12 weeks (3.4% vs 6.6%; RR 0.51, 95% CI 0.32–0.83; p = 0.009). Birth weight of both singletons (2971.0 ± 628.4 vs. 3118.8 ± 559.2 g; p = 0.004) and twins (2175.5 ± 494.8 vs. 2494.2 ± 584.7; p = 0.002) was significantly lower in the progesterone plus dydrogesterone versus progesterone group. Limitations, reasons for caution: The study were the open-label design and the non-randomized nature of the sequential administration of study treatments. However, our systematic comparison of the two strategies was able to be performed much more rapidly than a conventional randomized controlled trial. In addition, the single ethnicity population limits external generalizability. Wider implications of the findings: Oral dydrogesterone in addition to vaginal progesterone as luteal phase support in FET cycles can reduce the miscarriage rate and improve the live birth rate. Carefully planned prospective cohort studies with limited bias could be used as an alternative to randomized controlled clinical trials to inform clinical practice. Trial registration number: NCT03998761